Power Management of Hybrid Grid System With Battery Deprivation Cost Using Artificial Neural Network - Riyaz, Ahmed; Sadhu, Pradip Kumar; Iqbal, Atif; Tariq, Mohd; Urooj, Shabana; Alrowais, Fadwa (Frontiers in Energy Research, 2021)
Continuous power supply in an integrated electric system supplied by solar energy and battery storage can be maintained with the use of diesel generators. This paper discusses the optimum setting-point for isolated wind, PV, diesel, and battery storage electric grid systems. Optimal energy supply for hybrid grid (HG) systems means that the load is sufficient for 24 hours. This paper aims to integrate the battery deprivation costs as well as the fuel price feature in the optimization model, despite their major contributions to the HG battery method. In order to count charge-discharge cycles and measure battery deprivation, the Genetic algorithm concept is utilized. To solve the target function, an ANN-based algorithm with genetic coefficients also be used to optimize the power management system. In the objective function, a weight factor is proposed. Specific weight factor values are considered for simulation studies. On the algorithm actions, charging status, and its implications for the optimized expense of the hybrid grid, the weight factor effect is measured.